GONARTHRITIS:EXUDATE OR TRANSUDATE? - Mogila, A.A. (World of Medicine and Biology, 2017)
The study of joints has significantly improved over the past few decades from arthroplasty and biopsy to the use of arthroscopic and ultrasoundographic technologies that facilitate visualization and increase the reliability of synovial biopsy. But it is necessary to note a certain lack of understanding of some significant points about the causes and the development of synovitis. Our study provides a new understanding of the origin of this pathology and a new look at the solution to the problem of treating this disease. Objective: To explain the analysis of synovial fluid and determine the cause of its formation by the example of synovitis of the knee joint. The presence of lactate in the synovial fluid, we regarded as a direct sign that the synovial fluid is lactate. There are also indirect indications that the synovial fluid is lactic acid. We decided to find out if there is synovitis of the knee joint with an inflammatory effusion, as previously thought, or, according to our hypothesis, synovitis is lactic acid, which comes from the muscles.
Keywords: synovitis; synovial fluid; knee joint; ultrasound diagnosis; exudate; transudate; lactic acid